Penerapan Pemberian Virgin Coconut Oil (VCO) Melalui Massage Terhadap Pencegahan Luka Tekan Pasien Tirah Baring Di Ruang ICU RS PKU Muhammadiyah Karanganyar - Greynike Putri Astuti; Fida’ Husain; Andri Setiyawan (Jurnal Ventilator, 2023)
Bed rest is a condition when a person cannot move freely due to conditions that interfere with movement (activity). Pressure sores are one of the biggest impacts of bed rest. One of the interventions to prevent pressure sores is giving Virgin Coconut Oil (VCO) through massage. Aims; Knowing the results of the implementation of giving Virgin Coconut Oil (VCO) through Massage on the prevention of pressure sores on bed rest patients in the ICU Room of PKU Muhammadiyah Karanganyar Hospital. Method; This type of research is descriptive in the form of a case study. The approach used is the nursing care approach: planning, implementation, and evaluation. Respondents in this study amounted to two patients with a risk of pressure sores. The instrument uses an observation sheet and a Braden scale measurement questionnaire. Results; The results of the implementation showed that the Braden scale rose for both respondents for the first respondent, the Braden scale became 11, and for the second respondent, it became 15. Conclusion; There are differences in the Braden Scale in patients at risk of pressure sores after giving Virgin Coconut Oil (VCO) through Massage at PKU Muhammadiyah Karanganyar Hospital.